The Effects of Mandala Coloring Applied to Type 2 Diabetes Patients on Levels of Perceived Stress and Anxiety: A Randomized Controlled Study - Bahcecioglu Turan, Gulcan; Aslan, Senem (Mary Ann Liebert, Inc, 2025)
Aim: This randomized controlled study aimed to examine the effects of mandala coloring on perceived stress and anxiety levels in patients with type 2 diabetes. Method: This study was conducted between December 2023 and December 2024 with 92 inpatients in the endocrinology clinic of a university hospital. Patients were randomly assigned to the intervention group (n = 46) or control group (n = 46). The intervention group colored one mandala daily for 7 consecutive days, while the control group received routine care. Data were collected using the Personal Information Form, Perceived Stress Scale (PSS), and State Anxiety Scale (SAS). Statistical analyses were performed using two-way mixed ANOVA to examine group, time, and interaction effects, with Bonferroni correction applied for two primary outcomes. The study was reported in accordance with the CONSORT 2010 guidelines. Results: Compared with the control group, the intervention group showed significant reductions in the PSS total score (eta(2) = 0.122, p = 0.000), Inadequate Self-Efficacy subscale (eta(2) = 0.156, p < 0.001), Stress Perception subscale (eta(2) = 0.067, p = 0.013), and SAS score (eta(2) = 0.284, p = 0.000) after the intervention. No adverse events related to mandala coloring were reported. Conclusion: Mandala coloring effectively reduced perceived stress and state anxiety in patients with type 2 diabetes. It may be considered a feasible nursing intervention for the psychological management of these patients.
Keywords: anxiety; mandala coloring; nurse; perceived stress; type 2 diabetes